Penelusuran Metode Pembelajaran di MTs Darussalam Tambalang Dalam Keaktifan Dan Pemahaman Siswa Pelajaran Akidah Akhlak - Abdul Wahab Syakhrani; Sarinah; Salpiyah (Penerbit Lafadz Jaya, 2026)
This study aims to gain a deeper understanding of the various teaching methods used by teachers at MTs Darussalam Tambalang to help students become more active and improve their comprehension in the subject of Akidah Akhlak. The study used a descriptive qualitative approach, with data collected through direct observation, interviews, and documentation. The people involved in the study were the head of the madrasah, two Akidah Akhlak teachers, and students from grades VII to IX selected through a specific sampling method. Data analysis was carried out using the interactive model developed by Miles, Huberman, and Saldaña, which includes data processing, data presentation, and conclusion drawing. The results showed that the most commonly used methods were lecture, question and answer, group discussion, habituation, and storytelling. The use of varied methods that suit the situation was proven to increase student engagement and understanding. Therefore, teachers are encouraged to continue developing learning methods that are appropriate for the content of Akidah Akhlak.